ANALISIS DAMPAK PENGELUARAN PEMERINTAH DI BIDANG PENDIDIKAN TERHADAP PDB PER KAPITA: SPENDING MORE OR SPENDING BETTER - Achmad Rifa'i; Ganiko Moddilani (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2021)
Government spending is the first way to create quality human resources through budget allocation commitments in the education sector. In turn, a labor market filled with quality human resources will encourage welfare and productivity and it will impact the national economy. This study aims to analyze the relationship of government spending in education to the aggregate welfare proxied using GDP per capita. This study used time-series data 1980-2018 from World Development Indicators (WDI) World Bank. Vector Error Correction Model (VECM) is employed to analyze the government spending in the education sector to the welfare. Empirically, the findings of this study reveal that government spending in the education sector affects aggregate welfare with a little magnitude. The issue of equity and disparity in fiscal capacity among regions is the main matter. On the other side, Geographic, social, cultural, and population conditions are challenges that must be solved by the government.